Analisis Penerapan Strategi Pembelajaran Literasi Terpadu Melalui Model Cooperative Learning pada Kemampuan Membaca Kelas II SD - poppy rafina; nisa izzatul Jannah (Jurnal Dharma PGSD, 2026)
This study aims to describe the implementation of an integrated literacy learning strategy through the cooperative learning model to improve the reading skills of second-grade elementary school students. This study employed a qualitative approach with a descriptive research design. The data sources consisted of the classroom teacher and second-grade students involved in the learning process. Data were collected through observation, interviews, and documentation to obtain in-depth information regarding the implementation of the learning activities. The data were analyzed using an interactive analysis model, which included data reduction, data display, and conclusion drawing. The findings revealed that the implementation of an integrated literacy learning strategy through the cooperative learning model was able to create a more active, interactive, and enjoyable reading learning environment. Students became more enthusiastic in participating in learning activities, actively engaged in discussions, and helped one another understand reading materials. Although several challenges were identified, such as differences in students' reading abilities and limited instructional time, overall, the integrated literacy learning strategy through the cooperative learning model was found to support and improve the reading skills of second-grade elementary school students.